PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) di Kelas VII SMP Negeri 2 Kota Pagar Alam) - Mesi Fitriani (DIADIK, 2021)
This study aims to describe the application of the cooperative learning model type of STAD to increase student participation and learning achievement of the seventh grade students in PPKn subjects at SMP Negeri 2 Kota Pagar Alam. The research design used was classroom action research and quasi-experimental. The research subjects were students of class VII.a SMP Negeri 2 Pagar Alam even semester of the 2020/2021 school year. The quasi-experimental sample was class VII.b and class VII.c at SMP Negeri 2 Pagar Alam. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean (mean), percentage, and t-test. The results showed that the application of the cooperative learning model type STAD could increase participation and learning achievement of class VII students of SMP Negeri 2 Pagar ALam.